FLASH holographic microscopy using a compact extreme ultraviolet table top laser - Monserud, Nils C., author; Marconi, Mario, advisor; Menoni, Carmen, committee member; Wu, Mingzhong, committee member (Colorado State University. Libraries, 2015)
Microscopes allow our eyes to visualize objects at micro- and nanoscales. But there application are not limited to static images. The visualization of dynamic processes is necessary to understand complex systems on the micro- and nanoscales, Thus the need for microscopes capable of visualizing nanoscale processes, to further extend the development on micro- and nano-electromechanical devices (MEMS and NEMS). Conventional microscopy will not be sufficient for this purpose for two reasons the first is the spatial resolution is not sufficient to capture nanoscale objects and secondly if the object is moving out of plane the image taken needs to be adjusted using methods of post processing. To this end Fourier transform holography using and EUV light source was utilized to provide us with a method recording sub-micron oscillators. We recorded the oscillation of sub-micron pillars using time resolved extreme ultraviolet (EUV) Fourier transform Holography. The source utilized was a 46.9 nm tabletop capillary discharge with an EUV wavelength of 46.9nm, which provided large flux of coherent illumination. The bright illumination allowed for a modified Fresnel Zone plate to be used as a beam splitter. The modified Fresnel zone plate was able to produce a reference and object beam. This reference and object beam interfered creating a hologram. The reference wave is created by the first order focus while a central opening in the zone plate illuminates the object. Single-shot holograms allowed for the composition of a movie featuring the fast oscillation. Three-dimensional displacements of the object were determined as well by numerical back-propagation, or "refocusing" of the electromagnetic fields during the reconstruction of a single holography.
Keywords: holography; microscopy; extreme ultra-violet; soft x-ray; imaging